Effects of 2, 5-dimethylfuran fuel properties coupling with EGR (exhaust gas recirculation) on combustion and emission characteristics in common-rail diesel engines. (15th December 2015) - Chen, Guisheng; Di, Lei; Zhang, Quanchang; Zheng, Zunqing; Zhang, Wei
Abstract: The effects of DMF (2, 5-dimethylfuran) fuel properties combined with EGR (exhaust gas recirculation), CA50, EHN (2-Ethylhexyl nitrate) and multi-injection strategies on combustion and emission characteristics were experimentally investigated in two common-rail diesel engines including a single-cylinder engine and a multi-cylinder engine. Results demonstrate that, with DMF addition into diesel, ID (ignition delay) prolongs and smoke decreases more greatly as EGR rate increases. When DMF addition fraction increases up to 40%, the inherent trade-off between NO x and smoke can be eliminated, but the MPRR (maximum pressure rise rate) is too high. However, the higher MPRR can be reduced efficiently without serious penalties in smoke and BTE (brake thermal efficiency) by delaying CA50 and adding EHN reasonably. Although DMF and gasoline have very similar physic-chemical properties, DMF/diesel blends are much more efficient than gasoline/diesel wide-distillation blends to reduce soot with high EGR rates due to its much longer ID and atomic oxygen. With increasing DMF addition fraction, BTE is affected less by the delay of CA50, meanwhile, multi-injection strategies have less impact on soot generation. Additionally, as compared to the delay of CA50 and the addition of EHN, the employ of pilot injection is poor to reduced MPRR for DMF/diesel blends. Highlights: D40 can solve the NO x -smoke trade-off relationship, but leading to higher MPRR. Adding EHN into D40 can reduce MPRR efficiently with a little increase in soot. Compared to gasoline, DMF is much more efficient to reduce soot in CI engines. With DMF addition, multi-injection strategies have less impact on MPRR and soot. DMF may be a promising alternative for reducing soot emissions in CI engine LTC.